2014
DOI: 10.1063/1.4862260
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic anisotropy in cobalt-carbide nanoparticles

Abstract: An outstanding problem in nano-magnetism is to stabilize the magnetic order in nanoparticles at room temperatures. For ordinary ferromagnetic materials, reduction in size leads to a decrease in the magnetic anisotropy resulting in superparamagnetic relaxations at nanoscopic sizes. In this work, we demonstrate that using wet chemical synthesis, it is possible to stabilize cobalt carbide nanoparticles which have blocking temperatures exceeding 570 K even for particles with magnetic domains of 8 nm. First princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…The enhancement is driven by the modest interaction that changes the atomic structure and couples to selected orbitals to stabilize the orientation of the magnetic moment via the intrinsic SOI. The present work complements a recent development where metal-carbon nanoparticles with size ≈8 nm have been found to have blocking temperature (TB) in excess of 570 K [5]. These nanoparticles have layers of Co atoms separated by carbon layers and our studies have shown that the large MAE is driven by the reduced mixing between C and Co states.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…The enhancement is driven by the modest interaction that changes the atomic structure and couples to selected orbitals to stabilize the orientation of the magnetic moment via the intrinsic SOI. The present work complements a recent development where metal-carbon nanoparticles with size ≈8 nm have been found to have blocking temperature (TB) in excess of 570 K [5]. These nanoparticles have layers of Co atoms separated by carbon layers and our studies have shown that the large MAE is driven by the reduced mixing between C and Co states.…”
Section: Introductionsupporting
confidence: 78%
“…E(graphene), E(Co n ), and E(Co n on graphene) are the total energies of the graphene sheet, free Co n cluster, and that of the supported species, respectively. We find that Co 5 and Co 13 are bound to graphene with a BE of 1.02 and 2.24 eV, respectively, which are lower than the BE of a free Co-C dimer (3.20 eV). This indicates that the clusters are only moderately bound to graphene but enough to prevent the detachment and migration of clusters on the surface under ambient temperature.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…However, recent studies have indicated that the transition metal based nanoparticles where the transition metal layers are separated by carbon (C) layers, exhibit large MAE. 31,32 We have also shown recently that small Co clusters diluted with C undergo significant enhancement in MAE. 33 Such enhancement of MAE in transition metal carbide (TMC) results due to the mixing of p states of C with d states of transition metal.…”
Section: -13mentioning
confidence: 91%